Clinical and urodynamic features of the hypoactive detrusor in women - Encarnación-Cadenillas, Edwin (2023)
Objective: To describe the clinical and urodynamic features of the hypoactive detrusor (DU) in women. Methods: Cross sectional comparative study between two groups of women with lower tract urinary symptoms. Group 1 were patients with Pdet Qmax 30 or with the bladder emptying efficiency (BVE) criteria, and Group 2 were patients without DU. Central tendency measures and proportions were used to report results and parametric tests were performed to compare groups. Results: 155 patients were included, 44 with DU (Group 1) and 111 without DU (Group 2); mean age was 60,8 ± 16,3 and 55,7 ± 13,4 respectively (p=0,0468). Nocturia (p=0,0061) and micturition effort (p=0,000) were the only variables identified in the bivariate analysis who achieved statistical significance. Mean Watts factor (WF) was 3,2 ± 1,0 y 6,0 ± 2,2 in Group 1 and 2, respectively (p=0,000), while mean projected isovolumetric pressure 1 (PIP1) was 28,0 ± 7,5 and 45,9 ± 11,2, respectively (p=0,000). The multivariate analysis identified age above 60 years, nocturia and micturition effort associated with DU. Conclusion: Urodynamic parameters such as PIP1, BCI, BE and WF showed significant difference in the bivariate analysis, WF<5 and BCI <80 are best predictors of DU.